2021
DOI: 10.1038/s41598-021-88509-9
|View full text |Cite
|
Sign up to set email alerts
|

An open-label randomized controlled trial evaluating the efficacy of chloroquine/hydroxychloroquine in severe COVID-19 patients

Abstract: Despite several studies designed to evaluate the efficacy of chloroquine and hydroxychloroquine in the treatment of coronavirus disease 2019 (COVID-19), there is still doubt about the effects of these drugs, especially in patients with severe forms of the disease. This randomized, open-label, controlled, phase III trial assessed the efficacy of chloroquine or hydroxychloroquine for five days in combination with standard care compared to standard care alone in patients hospitalized with severe COVID-19. Chloroq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 28 publications
2
42
0
2
Order By: Relevance
“…Overall, 115 studies with 77,128 patients reported the number of patients requiring mechanical ventilation during the study period. We included ACEIs/ARBs, ammonium chloride, azithromycin, bamlanivimab, baricitinib plus remdesivir, bromhexine, budesonide, camostat mesilate, canakinumab, chloroquine, colchicine, convalescent plasma, dexamethasone, doxycycline, favipiravir, hydroxychloroquine, hydroxychloroquine plus azithromycin, hydroxychloroquine plus favipiravir, imatinib, INM005, interferon beta, intravenous immunoglobulin, ivermectin, lopinavir/ritonavir, methylprednisolone, recombinant human GCSF, remdesivir, sarilumab, sofosbuvir plus daclatasvir, sulodexide, tocilizumab, tofacitinib, vitamin D3 and SOC as treatment nodes in the NMA, for which observations came from 84 studies ( 3 , 6 , 22 26 , 28 31 , 35 , 42 , 43 , 46 , 47 , 50 , 53 , 55 , 57 61 , 63 , 64 , 66 , 67 , 71 , 73 77 , 79 , 80 , 82 , 83 , 85 87 , 89 , 92 94 , 96 100 , 102 , 105 107 , 109 , 111 118 , 120 124 , 126 , 128 132 , 134 , 135 , 139 , 140 , 145 , 151 , 152 , 154 156 ). About one-third (26/84) of the included studies were evaluated as low risk ( Supplementary Table 6 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 115 studies with 77,128 patients reported the number of patients requiring mechanical ventilation during the study period. We included ACEIs/ARBs, ammonium chloride, azithromycin, bamlanivimab, baricitinib plus remdesivir, bromhexine, budesonide, camostat mesilate, canakinumab, chloroquine, colchicine, convalescent plasma, dexamethasone, doxycycline, favipiravir, hydroxychloroquine, hydroxychloroquine plus azithromycin, hydroxychloroquine plus favipiravir, imatinib, INM005, interferon beta, intravenous immunoglobulin, ivermectin, lopinavir/ritonavir, methylprednisolone, recombinant human GCSF, remdesivir, sarilumab, sofosbuvir plus daclatasvir, sulodexide, tocilizumab, tofacitinib, vitamin D3 and SOC as treatment nodes in the NMA, for which observations came from 84 studies ( 3 , 6 , 22 26 , 28 31 , 35 , 42 , 43 , 46 , 47 , 50 , 53 , 55 , 57 61 , 63 , 64 , 66 , 67 , 71 , 73 77 , 79 , 80 , 82 , 83 , 85 87 , 89 , 92 94 , 96 100 , 102 , 105 107 , 109 , 111 118 , 120 124 , 126 , 128 132 , 134 , 135 , 139 , 140 , 145 , 151 , 152 , 154 156 ). About one-third (26/84) of the included studies were evaluated as low risk ( Supplementary Table 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…The hospital discharge rate was reported in 65 studies including 53,636 patients and 34,247 events. Treatment nodes included in the network were azithromycin, bamlanivimab, baricitinib plus remdesivir, camostat mesilate, canakinumab, convalescent plasma, dapagliflozin, dexamethasone, favipiravir, hydroxychloroquine, hydroxychloroquine plus azithromycin, hydroxychloroquine plus favipiravir, interferon beta, ivermectin, lopinavir/ritonavir, mesenchymal stem cells, remdesivir, sarilumab, tocilizumab, tofacitinib and SOC, which were investigated in 48 studies ( 3 , 6 , 22 26 , 31 , 43 , 46 , 55 , 57 , 64 , 71 73 , 76 , 80 , 82 , 84 , 89 , 91 , 93 , 96 98 , 100 , 101 , 106 , 107 , 109 , 110 , 115 , 116 , 121 , 122 , 124 , 126 , 128 132 , 145 147 , 157 , 158 ). Out of the 48 studies included in the NMA, 19 were evaluated as low risk ( Supplementary Table 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Hydroxychloroquine, as a treatment for malaria, has also received widespread attention. Hydroxychloroquine has been shown to have a certain effect on the treatment of patients with mild disease; however, in patients with severe COVID-19, the use of hydroxychloroquine resulted in significant worsening of clinical status because of renal dysfunction and increased need for invasive mechanical ventilation ( 37 ). The clinical use of hydroxychloroquine still needs to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxychloroquine has been one of these drugs. Several clinical trials and in vitro studies have reported promising results in the early stages regarding the role of hydroxychloroquine in the treatment of COVID-19, while subsequent observational studies and clinical trials have reported no effect of hydroxychloroquine (Gautret et al 2020 ; Chen et al 2020a ; Kamran et al 2020 ; Réa-Neto et al 2021 ; Tang et al 2021 ). The open-label Randomized Evaluation of COVID-19 Therapy (RECOVERY) trial in the United Kingdom announced the early closure of the hydroxychloroquine arm after finding that among patients hospitalized with COVID-19 who received hydroxychloroquine did not have lower mortality rates at 28th day compared to those who received usual care.…”
Section: Discussionmentioning
confidence: 99%
“…Chloroquine and hydroxychloroquine are the most discussed drugs among the repurposing drugs tried as potential therapeutic agents in the treatment of COVID-19. Although initial studies have shown that chloroquine and hydroxychloroquine to be beneficial in the treatment of COVID-19, recent clinical studies lacking critical pharmacology considerations and reliable drug quantifications to ensure optimal dosing and standardization have provided conflicting results (Gautret et al 2020 ; Chen et al 2020a ; Kamran et al 2020 ; Réa-Neto et al 2021 ; Tang et al 2021 ). Hydroxychloroquine has antimalarial, anti-inflammatory, immunomodulatory, anti-infective, antitumoral, metabolic and antithrombotic effects.…”
Section: Introductionmentioning
confidence: 99%